Design and Fabrication of a Bicycle Sprayer - Abdullateef, Ahmed Abiola; Lawal, Sadiq Susi; Aliyu, Yusuf; Kehinde, Olajide Tomiwa; Dickson, Simeon (ABUAD Journal of Engineering Research and Development (AJERD), 2024)
The bicycle sprayer designed for crop spraying is a pragmatic and environmentally friendly choice for small-scale farmers, providing both effectiveness and long-term viability. Engineered to be attached on a regular bicycle, this device enables farmers to easily traverse fields and agricultural area with minimal physical effort. The sprayer features a 20-liter tank, suitable for small-scale farms, equipped with a slide-crank pumping system and a precision nozzle assembly to ensure efficient spraying. Made from lightweight and sturdy materials, it is both cost-efficient and highly portable. The rear wheel’s rotation is converted into translation motion of the rod and pump by the use of a slider-crank reciprocating mechanism. The bicycle sprayer doubles as a mode of transportation for farmers or users traveling to and from the farm, enhancing its utility. The bicycle sprayer provides an environmentally-friendly option for small-scale farmers, enhancing crop productivity and minimizing the risks associated with liquid chemicals for farmers or operators. Based on the performance outcome, the recently created sprayer is capable of covering an area of one hectare in one hour. It demonstrates improved spray consistency and achieves a 75% efficiency rate, as confirmed through a sequence of tests conducted on specific farms.